New insights into HLA‐G mediated tolerance. Issue 3 (13th August 2014) - Amodio, G.; Sales de Albuquerque, R.; Gregori, S.
Abstract Human Leukocyte Antigen G (HLA‐G) is a nonclassical HLA class I molecule with well‐characterized immunomodulatory activities. HLA‐G was first described as a regulatory molecule that allows the fetus to elude the maternal immune response. In the last decade it has become evident that HLA‐G is involved in modulating both innate and adaptive immune responses, in maintaining tolerance in autoimmune and inflammatory diseases and after transplantation, and in promoting immune escape in cancer and infectious diseases. HLA‐G exerts its modulatory/regulatory functions directly by interacting with specific inhibitory receptors. The expression of HLA‐G is finely tuned by genetic variations in the noncoding region of the locus. The recent discovery of dendritic cells‐10 (DC‐10) as naturally occurring HLA‐G‐expressing dendritic cells opens new perspectives in the identification of the molecular and cellular mechanisms underlying HLA‐G‐mediated tolerance. An overview on the HLA‐G‐mediated inhibition of innate and adaptive immune cells, on the genetic influence on HLA‐G expression, and on HLA‐G‐expressing DC‐10 is presented. Moreover, we discuss the central and critical role of DC‐10 in the HLA‐G‐mediated tolerance.